A WARRANTY SERVICING STRATEGY FOR A PRODUCT USED INTERMITTENTLY - D. SITANIA (NIM: 23407029); Pembimbing: Prof. Dr. Bermawi P. Iskandar, FARIDA
Durable products, as electronic appliances and automobiles, are sold with a warranty. Selling a product with warranty causes additional costs to the manufacturer to rectify the failed product under warranty. Three ways that can be used to reduce the warranty costs are improving product reliability, conducting preventive maintanance, and applying warranty servicing strategy. Most of papers dealing with warranty servicing strategies assume that products are used continuously. In the some situation, the products are used intermittently such as elevator, electric starter of motorcycle, emergency generator, etc. This research is focused on a servicing strategy for a product used intermittently. The servicing strategy involves repair and replacement, and it its devided into two intervals ie., (0, W1) and (W1, W). The first failure in the second interval is replaced by a new product, and all other failures are minimally repaired. The objective is to determine W1* which minimises the expected warranty cost per unit sold. Numerical example is given to illustrate the optimal solution, W1*, and its expected warranty cost.